Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity